The Effect of Spiritual Well-Being on Self-care Agency in Chronic Obstructive Pulmonary Patients in Turkey: The Mediating Role of Psychological Resilience - Öztürk, Zeynep; Turan, Gülcan Bahcecioglu; Aksoy, Meyreme (Springer, 2024)
The aim of the present study was to determine the mediator role of psychological resilience in examining the effect of spiritual well-being on self-care agency in Chronic Obstructive Pulmonary Patients (COPD). The present cross-sectional and correlational study has a descriptive design, and it was conducted with 200 COPD patients admitted to the chest diseases outpatient clinic of a university hospital. "Spiritual Well-Being Scale (FACIT Sp-12)," "Brief Resilience Scale (BRS)" and "Self-Care Agency Scale (SCAS)" were used in the study for collecting the research data. STROBE recommendations were followed while reporting this study. FACIT Sp-12 total score average, the BRS total average score and the ASAS total average score of the patients were found to be 29.88 ± 1.44, 21.47 ± 66.31, and 84.81 ± 14.69, respectively. In addition, it was determined that both spiritual well-being (? = 0.170) and psychological resilience (? = 0.777) positively affected self-care agency. SCAS mediates the effect of FACIT-Sp-12 on self-care agency and strengthens the positive effect of FACIT-Sp-12 on self-care agency (? = 0.843). It was seen that the predictive effect of these two variables in explaining self-care power was 60%. Spiritual well-being and self-care agency of the COPD patients were found to be moderate, and the psychological resilience was found to be high. In addition, spiritual well-being was found to affect self-care agency directly and the mediating role of psychological resilience indirectly. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023. Springer Nature or its licensor (e.g. a society or other partner) holds exclusive rvalues ights to this article under a publishing agreement with the author(s) or other rightsholder(s); author self-archiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.
Keywords: Chronic obstructive pulmonary disease; Nurse; Resilience; Self-care; Spirituality